2022
DOI: 10.3389/fmicb.2022.1000822
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of bovine lactoferrin against Gardnerella species clinical isolates

Abstract: Gardnerella species play a key role in the development and recurrence of Bacterial Vaginosis (BV), a common imbalance of the vaginal microbiota. Because of the high rates of BV recurrence reported after treatment with standard of care antibiotics, as well as the emergence of antibiotic-resistant BV, the development of alternative treatment approaches is needed. Bovine lactoferrin, a well studied iron-binding glycoprotein with selective antimicrobial activity, may ameliorate vaginal dysbiosis either alone or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Prebiotics have also been tested in combination with antibiotics. Very recently was studied the antimicrobial activity of bovine lactoferrin alone or in combination with metronidazole or clindamycin against G. vaginalis isolates, and the results showed inhibition of Gardnerella growth in a dose‐dependent effect and the combination with clindamycin resulted in a synergistic effect (Pino et al, 2022 ).…”
Section: Promising Alternative Strategies For Bv Treatmentmentioning
confidence: 99%
“…Prebiotics have also been tested in combination with antibiotics. Very recently was studied the antimicrobial activity of bovine lactoferrin alone or in combination with metronidazole or clindamycin against G. vaginalis isolates, and the results showed inhibition of Gardnerella growth in a dose‐dependent effect and the combination with clindamycin resulted in a synergistic effect (Pino et al, 2022 ).…”
Section: Promising Alternative Strategies For Bv Treatmentmentioning
confidence: 99%
“…Proteolysis was stopped at the time points indicated by mixing with SDS PAGE sample buffer and heating to 90 °C iron-binding capacity persists for that duration. Moreover, our recent in vitro experiments (Pino et al 2022) have shown that MTbLF has antimicrobial activity against clinical isolates of Gardnerella vaginalis, a key pathogen in the development and recurrence of BV. The ratio of 80 kDa bLF to its 43 kDa and 37 kDa fragments remains high (> 80%) over at least the first 12 h of the time course while the tablet is in the Dissolution phase or early Washout phase.…”
Section: Implications For Clinical Dosingmentioning
confidence: 99%
“…First-line treatment for BV includes the use of topical or systemic antibiotics, such as metronidazole and clindamycin, whereas polyenes (e.g., nystatin) and azoles are usually administrated in the case of VVC [14]. Unfortunately, antibiotics and antifungal drugs are not always effective, since the microorganisms responsible for BV and VVC can resist these treatments by forming biofilms or by acquiring resistance [15,16]. In addition, antibiotics do not act selectively on the causative agent of the infection and negatively affect endogenous lactobacilli, in turn promoting BV and potentially VVC recurrence [17].…”
Section: Introductionmentioning
confidence: 99%